1995
DOI: 10.1002/ange.19951072341
|View full text |Cite
|
Sign up to set email alerts
|

Flüssige 1,3‐Dialkylimidazoliumsalze als Lösungsmittel für die Katalyse in Zweiphasensystemen: durch Rhodiumkomplexe katalysierte Hydrierung, Isomerisierung und Hydroformylierung von Alkenen

Abstract: Eine deutliche Erweiterung des Anwendungsbereiches der Zweiphasenkatalyse bringen ionische Flüssigkeiten von Typ 1. Denn nun können auch in Wasser nur wenig lösliche oder instabile Substrate, Komplexe und Liganden für diese industriell hochinteressante Variante der Homogenkatalyse eingesetzt werden .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 15 publications
0
33
0
5
Order By: Relevance
“…[1] This lack of special requirements enhances the attractiveness of using ionic liquids as immobilizing agents allowing facile catalyst recycling whilst maintaining the characteristic selectivity of molecular catalysts. In addition, it has been observed that the ligand effects typical of some homogeneous processes remain operative under such biphasic conditions, [2] suggesting the occurrence of similar reaction mechanisms in both media, and indicating that our current understanding of structure/function relationships in solution could also be used for catalyst improvement in ionic liquids. Nevertheless, other studies have found reaction selectivities strongly dependent on the features of the ionic liquid, [3] evidencing possible non-innocent roles of these immobilizing media during catalysis.…”
Section: Introductionmentioning
confidence: 97%
“…[1] This lack of special requirements enhances the attractiveness of using ionic liquids as immobilizing agents allowing facile catalyst recycling whilst maintaining the characteristic selectivity of molecular catalysts. In addition, it has been observed that the ligand effects typical of some homogeneous processes remain operative under such biphasic conditions, [2] suggesting the occurrence of similar reaction mechanisms in both media, and indicating that our current understanding of structure/function relationships in solution could also be used for catalyst improvement in ionic liquids. Nevertheless, other studies have found reaction selectivities strongly dependent on the features of the ionic liquid, [3] evidencing possible non-innocent roles of these immobilizing media during catalysis.…”
Section: Introductionmentioning
confidence: 97%
“…More specifically, salts that are liquids at ambient temperature have received much attention because of their potential as direct replacements for conventional solvents and as a means to immobilize transition-metal catalysts in biphasic processes. [3][4][5] Many organic reactions have been carried out in ionic liquids, such as hydrogenation, [6,7] oxidation, [8] epoxidation, [9] and hydroformylation reactions. [10] The use of ionicliquid media for other classic transformations, such as Friedel-Crafts acylation [11] and alkylation [12] reactions, allylation, [13,14] Diels-Alder, [15] and Heck [16] reactions, as well as Suzuki [17] and Trost-Tsuji coupling [18] reactions in ionic liquids have also been reported.…”
mentioning
confidence: 99%
“…In opposition when dissolved in solvents of relatively low dielectric constants such as CDCl 3 they form contact ion pairs (via C-H …. π bonds) as observed by 1 H NOESY NMR experiments with BMI.BPh 4 . 60 The apparent volumes for the cation and anion, calculated from 13 C-NMR relaxation times, increases with an increase in the concentration indicating the formation of floating aggregates through hydrogen bonds.…”
Section: Structural Organization In Solutionmentioning
confidence: 66%
“…Soon after the first reports on the syntheses and applications in organometallic catalysis of the air stable room temperature ionic liquids (RTILs) 1-n-butyl-3-methylimidazolium tetrafluoroborate (BMI.BF 4 ), hexafluorophosphate (BMI.PF 6 ) and their analogues 1 in the middle of the 1990s a renaissance of the rich chemistry of molten salts 2 has begun and continues to flourish. 1,3-Dialkylimidazolium cations associated with relatively weak coordinating anions such as tetrafluoroborate, hexafluorophosphate, trifluoromethane sulfonate, etc.…”
Section: Introductionmentioning
confidence: 99%